2018
DOI: 10.1002/jbm.b.34071
|View full text |Cite
|
Sign up to set email alerts
|

Self‐production of oxygen system CaO2/MnO2@PDA‐MB for the photodynamic therapy research and switch‐control tumor cell imaging

Abstract: Photodynamic therapy (PDT) holds promise in biochemical study and tumor treatment. A novel multifunctional nanosystem CaO /MnO @polydopamine (PDA)-methylene blue (MB) nanosheet (CMP-MB) was designed. CaO nanoparticles were encapsulated by MnO nanosheet, and then PDA was coated on the surface of CaO /MnO nanosheets, which could adsorb photosensitizer MB through hydrophobic interaction or π-π stacking. In this nanosystem, CaO /MnO had the ability of self-production of oxygen, which solved the problem of tumor hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…Once exposed to a tumor microenvironment, the MnO 2 NSs could decompose into Mn 2+ , which triggered the emission of MB fluorescence. Hence, switch-controlled tumor cell imaging was achieved 84. Xia et al found that the MnO 2 NS mediated quenching effect can be reversed via the reduction of MnO 2 into Mn 2+ by ascorbic acid (AA), resulting in MnO 2 NS destruction.…”
Section: Biomedical Applications Of Mno2 Nanosheets (Mno2 Nss)mentioning
confidence: 99%
“…Once exposed to a tumor microenvironment, the MnO 2 NSs could decompose into Mn 2+ , which triggered the emission of MB fluorescence. Hence, switch-controlled tumor cell imaging was achieved 84. Xia et al found that the MnO 2 NS mediated quenching effect can be reversed via the reduction of MnO 2 into Mn 2+ by ascorbic acid (AA), resulting in MnO 2 NS destruction.…”
Section: Biomedical Applications Of Mno2 Nanosheets (Mno2 Nss)mentioning
confidence: 99%
“…To date, several preparation methods of MO 2 are developed, including hydrolyzation-precipitation method [ 22 , 23 ], underwater Leidenfrost dynamic chemistry method [ 24 ], reversed-phase microemulsion method [ 25 ], gas diffusion method [ 26 ], and sonochemical method [ 27 ]. Due to the instability of MO 2 , some surface modification is necessary to achieve better applications in biomedical fields, frequently used surface modifiers are polyethylene glycol (PEG), polyvinyl pyrrolidone (PVP), CO-520, and hyaluronic acid (HA) [ 23 , 25 , 28 , 29 ]. Proper surface modification not only increases the stability of MO 2 , but also improves the dispersion of nanoparticles (NPs), even be possible to target the tumor.…”
Section: Synthesis and Surface Modification Of Momentioning
confidence: 99%
“… MO 2 Preparation Morphology and size Surface modifier Applications Ref. CaO 2 Hydrolyzation-precipitation method Particle, <5 nm SH Calcium-overload/Oxidation therapy [ 20 ] CaO 2 Hydrolyzation-precipitation method Particle, 15 ± 10 nm PEG-200 PDT [ 22 ] CaO 2 Hydrolyzation-precipitation method Spherical structure, 5–15 nm PEG-200 PDT [ 23 ] CaO 2 Hydrolyzation-precipitation method Particle PVP PDT [ 28 ] CaO 2 Hydrolyzation-precipitation method Particle, 107 ± 11 nm HA CDT [ 29 ] CaO 2 Hydrolyzation-precipitation method Clusters, 300 ± 20 nm PEG-200 PDT [ 30 ] CaO 2 Hydrolyzation-precipitation method Spherical structure, 116.0 ± 7.6 nm PEG-200 PDT [ 31 ] CaO 2 Hydrolyzation-precipitation method Particle, <200 nm PEG-200 Chemotherapy/CDT ...…”
Section: Synthesis and Surface Modification Of Momentioning
confidence: 99%
See 1 more Smart Citation
“…Reversing a hypoxic state in a tumor was also shown to impede the MDSC-regulated pathway ( 55 , 56 ). Hypoxia is produced by consuming oxygen after making ATP (adenosine triphosphate), thus, reversing it can be achieved by interfering with oxidative phosphorylation ( 57 , 58 ). This study used platelet membranes as nano-carriers called PM-IR780-Met, which included encapsulated metformin whose role was to decrease oxygen consumption by inhibiting the mitochondrial respiratory chain.…”
Section: Inhibition Of Mdscsmentioning
confidence: 99%